Breast cancer chemoprevention. Issue 2 (February 2012) - Gabriel, Emmanuel M; Jatoi, Ismail
According to the National Cancer Institute Surveillance Epidemiology and End Results Cancer Statistics Review, the incidence of invasive breast cancer in the USA is 124 women per 100, 000 population. Women at increased risk for breast cancer have three major options to reduce their risk, specifically screening, chemoprevention and prophylactic surgery. In this article, we focus on chemoprevention. There are three chemoprevention agents available to reduce breast cancer risk: tamoxifen, raloxifene and exemestane. In this article, we summarize the major randomized clinical trials investigating the use of these agents in the chemoprevention setting. Randomized controlled trials have shown that these agents can reduce breast cancer incidence, but the potential risks of these agents and their impact on quality of life should also be carefully considered. Indeed, it is always important to keep in mind that chemoprevention targets asymptomatic women, and therefore the decision to embark on this strategy should never be taken lightly.